Education and Female Agency in the Garden: Doris Lessing’s “Flavors of Exile” - García Navarro, Carmen (Miscelánea: A Journal of English and American Studies, 2021)
Doris Lessing’s recent centenary brought opportunities to look at her works with fresh eyes. This is also the case with Lessing’s interest in education (Cairnie 2008; Sperlinger 2017), especially that of children in their transition to youth. This paper argues that this was an interest with which Lessing consistently concerned herself in both her fiction and non-fiction writings. Using the corpus of her African short stories as a primary reference framework, this paper studies “Flavours of Exile” (1957), a short story in which a family’s vegetable garden becomes a learning space for informal experimentation. The story is used by Lessing as a platform to raise her concerns about the education of the female subject in the historical context of decolonisation.